Screening and fermentation medium optimization of a strain favorable to Rice–fish Coculture - Xia, Banghua; Zou, Haobo; Li, Linyuan; Zhang, Bitao; Xiang, Yifang; Zou, Yuning; Shen, Zhentao; Xue, Shuqun; Han, Ying (Frontiers in Microbiology, 2022)
Rice–fish coculture (RF) is a small ecosystem in which microorganisms are widely distributed in the fish, water environment, soil, and plants. In order to study the positive effects of microorganisms on common carp and rice in the RF ecosystem, a total of 18 strains with growth-promoting ability were screened from common carp (Cyprinus carpio) gut contents, among which three strains had the ability to produce both DDP-IV inhibitors and IAA. The strain with the strongest combined ability, FYN-22, was identified physiologically, biochemically, and by 16s rRNA, and it was initially identified as Bacillus licheniformis. As the number of metabolites secreted by the strain under natural conditions is not sufficient for production, the FYN-22 fermentation medium formulation was optimized by means of one-factor-at-a-time (OFAT) experiments and response surface methodology (RSM). The results showed that, under the conditions of a soluble starch concentration of 10.961 g/L, yeast concentration of 2.366 g/L, NH4Cl concentration of 1.881 g/L, and FeCl3 concentration of 0.850 g/L, the actual measured number of FYN-22 spores in the fermentation broth was 1.913 × 109 CFU/mL, which was 2.575-fold improvement over the pre-optimization value. The optimized fermentation solution was used for the immersion operation of rice seeds, and, after 14 days of incubation in hydroponic boxes, the FYN-22 strain was found to have a highly significant enhancement of 48.31% (p < 0.01) on the above-ground part of rice, and different degrees of effect on root length, fresh weight, and dry weight (16.73%, 17.80%, and 21.97%, respectively; p < 0.05).